2020
DOI: 10.1128/iai.00400-20
|View full text |Cite
|
Sign up to set email alerts
|

Limited Role of Mincle in the Host Defense against Infection with Cryptococcus deneoformans

Abstract: Cryptococcus deneoformans is an opportunistic fungal pathogen that frequently causes fatal meningoencephalitis in patients with impaired cell-mediated immune responses such as AIDS. Caspase-associated recruitment domain 9 (CARD9) plays a critical role in the host defense against cryptococcal infection, suggesting the involvement of one or more C-type lectin receptors (CLRs). In the present study, we analyzed the role of macrophage-inducible C-type lectin (Mincle), one of the CLRs, in the host defense against C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…These observations suggest that the ability of APCs to produce IL-1β and IL-23 may not differ between WT and Jα18KO mice, and that IL-17A and IL-22 production may be caused by the activated iNKT cells. IL-17A and IL-22 are known to contribute to the epithelial barrier function against bacterial infection through inducing the production of AMPs, including β-defensins and S100 proteins [ 11 , 39 ]. Consistent with the results of previous studies, we found that AMP production was significantly reduced in Jα18KO mice compared with that of WT mice, which was accompanied by the reduced production of IL-17A and IL-22.…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest that the ability of APCs to produce IL-1β and IL-23 may not differ between WT and Jα18KO mice, and that IL-17A and IL-22 production may be caused by the activated iNKT cells. IL-17A and IL-22 are known to contribute to the epithelial barrier function against bacterial infection through inducing the production of AMPs, including β-defensins and S100 proteins [ 11 , 39 ]. Consistent with the results of previous studies, we found that AMP production was significantly reduced in Jα18KO mice compared with that of WT mice, which was accompanied by the reduced production of IL-17A and IL-22.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that GlcCer immunization protected the host from C. neoformans infection 57) . In our previous study, Mincle, a CLR, recognized fungal β -GlcCer and induced the Th22 immune response after infection with C. deneoformans 58) . Nucleic acids of pathogens induce an inflammatory response.…”
Section: Cell Wallmentioning
confidence: 91%
“…Isotype-matched IgG was used for control staining. The stained cells were analyzed using a BD FACS Canto II flow cytometer (BD Bioscience) as previously described 11 , 31 33 .…”
Section: Methodsmentioning
confidence: 99%